1959
DOI: 10.1039/jr9590003404
|View full text |Cite
|
Sign up to set email alerts
|

687. Organosilyloxy-derivatives of metals. Part I. Alkylsilyloxy-derivatives of titanium, zirconium, niobium, and tantalum

Abstract: or 0, M = Ti, Zr, Nb, or Ta, and n is the valency of M, have been prepared by various methods. Their physicochemical properties have been studied and are compared with the corresponding metal tertiary alkoxides. The organosilyloxy-metal compounds appear to be less susceptible to hydrolysis or thermal decomposition than the metal tertiary alkoxides.TETRAKISTRIMETHYLSILYLOXYTITANIUM Ti(O*SiMe,), was first reported by English and Sommerl in 1955. Although other authors2*3*4s5 have since prepared this and other tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

1961
1961
2013
2013

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…Evaporation in vacuo a t room temperature gave as condensate a small quantity of silanol, hexainethyldisiloxane, and water, and left a liquid containing a white precipitate (1). The formation of silanol, disiloxane, and water suggested that some hydroxy compounds, e.g.…”
Section: Results a N D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaporation in vacuo a t room temperature gave as condensate a small quantity of silanol, hexainethyldisiloxane, and water, and left a liquid containing a white precipitate (1). The formation of silanol, disiloxane, and water suggested that some hydroxy compounds, e.g.…”
Section: Results a N D Discussionmentioning
confidence: 99%
“…In a previous communication (1) we reported the preparation and properties of some trialkylsilyloxy derivatives of titanium, zirconium, niobium, and tantalum. I t was observed that these compounds were less susceptible to hydrolysis than the metal alkoxides and it was suggested that this property was connected with the water-repellant nature of the trialkylsilyloxy group.…”
Section: Introductionmentioning
confidence: 99%
“…The solid product was purified by sublimation under vacuum. Analysis by general methods (8) Hydrolysis was carried out in dioxane which had been refluxed over sodium for several hours and fractionally distilled. A weighed amount of the silyloxide (2.0-2.5 g) was dissolved in dioxane (30 g) at room temperature, and a weighed amount of water ( h mole per mole metal atoms) was added to the stirred solution.…”
Section: Methodsmentioning
confidence: 99%
“…All hydrolysis products were analyzed for aluminum and silicon (8) and their molecular weights were determined by cryoscopy in cyclohexane. Infrared spectra were recorded for several products at concentrations of 3.0, 4.0, 5.0, and 6.0 wt.% in cyclohexane, using KBr cells of path length 0.1 mm and a Beckman IR-7 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Metals, except vanadium, were determined gravin~etrically a s the ignited oxides (A), and silicon a s silica (4). An oxidation inethod ( 5 ) was used for the determination of ethoxy and isopropoxy groups, and basic nitrogen was estimated in a modified I<jeldahl apparatus (I).…”
Section: -L7zalysismentioning
confidence: 99%